Stone Wool Substrate Cover Incision Impacts on the Root-Zone Water Content, Temperature, and Yield of Tomato Cultures - Ahn, Tae In; Yang, Jung-Seok; Im, Yong-Hoon; Youn, Young Jik; Lee, Ju Young (Frontiers in Plant Science, 2022)
Standardized cultivation systems are crucial for establishing reproducible agronomic techniques. Especially stone wool-based cultivation is governed by standardized specifications and provides a controllable root-zone environment. However, the effects of stone wool cover incision on root-zone variability have rarely been studied. Therefore, in this study, we focused on the effect of the stone wool cover incision method on environmental variations and their subsequent effects on tomato plant productivity. Stone wool slab plastic covers represent a core component of this substrate system that can potentially affect the performance of water control techniques. We designed a cover incision method to create four different levels of drainage performances that were tested by cultivating tomato plants (Solanum lycopersicum ‘Dafnis’). The water content, root-zone temperature, and dissolved oxygen were measured and analyzed relative to the tomato yield. We found that the incision level with the lowest drainage performance showed a lower air-root zone temperature correlation slope than those of slabs with favorable drainage conditions. Furthermore, these slabs had low dissolved oxygen levels (3.2 mg/L); nevertheless, the tomatoes grown in the slabs with incision level showing the lowest drainage performance had greater fruit yield (6748 g/plant) than those in the slabs with favorable drainage conditions (6160 g/plant). Furthermore, the normalized yield separation timing between treatments coincided with the hotter air temperature (27 ℃ average) periods. We noted that manipulating the cover incision process consequently entailed variations in the correlation slope between the air temperature and root-zone temperature in the substrate. Our results reveal another trade-off relationship in the conventional perspective on the drainage performance effects and provide insights into further optimization of crop production and water use in the stone wool-based system.